2020
DOI: 10.1177/1178633720905977
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Ceftolozane-Tazobactam for the Treatment of Serious Pseudomonas aeruginosa Infections in Saudi Tertiary Care Center

Abstract: Introduction: Multidrug-resistant Pseudomonas aeruginosa isolates have multiple resistance mechanisms, and there are insufficient therapeutic options to target them. Ceftolozane-tazobactam is a novel antipseudomonal agent that contains a combination of an oxyimino-aminothiazolyl cephalosporin (ceftolozane) and a β-lactamase inhibitor (tazobactam). Methods: A single-center retrospective observational study between January 2017 and December 2018 for patients who had been diagnosed with carbapenem-resistant P aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…Five countries were included: USA (12 studies [ 22 , 24 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 37 , 39 , 40 ]), Spain (4 studies [ 23 , 26 , 31 , 41 ]), Saudi Arabia (3 studies [ 21 , 25 , 42 ]), the UK (2 studies [ 36 , 38 ]), and France (1 study [ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Five countries were included: USA (12 studies [ 22 , 24 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 37 , 39 , 40 ]), Spain (4 studies [ 23 , 26 , 31 , 41 ]), Saudi Arabia (3 studies [ 21 , 25 , 42 ]), the UK (2 studies [ 36 , 38 ]), and France (1 study [ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, P. aeruginosa is among the top six bacterial species responsible for nosocomial infections, and the second most common pathogen causing ventilator-associated pneumonia and catheter-related urinary tract infections [2]. Despite advences in critical-care management, P. aeruginosa infections are associated with a mortality rate reaching 20% -50% [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), [ 21 , 22 , 24 , 27 29 , 33 , 34 , 39 41 , 43 45 , 50 , 51 , 54 , 56 , 57 , 59 , 61 , 62 , 68 71 , 73 – 77 , 79 – 85 , 87 – 92 , 94 , 95 , 97 – 100 ] Spain (N = 15) [ 26 , 28 , 30 32 , 35 37 , 42 , 47 , 49 , 58 , 66 , 79 , 96 ], and Italy (N = 13) [ 18 , 20 , 23 , 25 , 48 , 52 , 53 , 55 , 64 , 67 , 72 , 79 , 86 ]. A variety of study designs were captured: 27 were non-comparative retrospective studies [ 18 , 19 , 22 , 24 , 25 , 28 , 32 , 33 , 40 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
“…All 47 studies that included more than one patient reported clinical outcomes with C/T treatment: 39 reported clinical outcomes [ 18 21 , 23 43 , 81 , 83 – 86 , 90 , 92 , 94 – 100 ], 19 reported microbiological outcomes [ 19 , 21 , 24 , 31 33 , 35 38 , 40 , 41 , 43 , 80 , 94 , 96 – 98 , 100 ], and 45 reported mortality rates [ 18 43 , 79 , 80 , 82 – 92 , 94 – 98 , 100 ]. Clinical success rates ranged from 45.7 to 100.0%, with 27 studies (69%) reporting clinical success rates of > 70%.…”
Section: Resultsmentioning
confidence: 99%